Management of metastatic castration-resistant prostate cancer: Insights from urology experts in Thailand - Bannakij Lojanapiwat (2018)
© 2017 Treatment options for castration-resistant prostate cancer (CRPC) are available, but clear instructions for the selection of appropriate treatment are lacking. A meeting of urology experts based in Thailand was convened with the following objectives: (1) to reach a consensus and share real-life experiences about how to identify CRPC; (2) to choose the appropriate treatment for CRPC patients; (3) to evaluate disease progression using novel inhibitors of the androgen receptor pathway; (4) to identify the frequency of monitoring disease; and (5) to promote rational use of corticosteroids in CRPC patients. This consensus document can provide guidance to other urologists in Thailand to provide appropriate treatment to metastatic CRPC patients in a timely manner.